OPTIMALISASI HASIL BELAJAR MELALUI PEMBELAJARAN PROBLEM BASED LEARNING DENGAN PENDEKATAN CULTURALLY RESPONSIVE TEACHING KULINER KHAS MADIUN MATERI STATISTIKA - Fitria, Ruina Nur; Sardulo Gembong; Lilik Sulistyawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to optimise mathematics learning outcomes by implementing the problem-based learning (PBL) model combined with the culturally responsive teaching (CRT) approach in the context of Madiun's culinary specialities in statistics material. The research method used is classroom action research (CAR. The subjects of this study were students of class VIII A of SMPN 14 Madiun. Data were collected through learning outcome tests and observations. The results of the study indicate that the application of PBL with the CRT approach in the context of Madiun's culinary specialities can improve students' understanding and skills in statistical material. In addition, students become more motivated and active in the learning process because the material taught is relevant to their local culture. This increase can be seen from the average value of students in each cycle and the positive response from students to learning. Thus, the application of PBL with the CRT approach based on Madiun's culinary specialities has proven effective in optimising student learning outcomes in statistical material. Therefore, the researcher recommends that teachers consider using a similar approach when teaching other materials to improve student learning outcomes.